Information Computing and Applications First International Conference, ICICA 2010, Tangshan, China, October 15-18, 2010. Proceedings - Zhu, Rongbo; Zhang, Yanchun; Liu, Baoxiang; Liu, Chunfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the First International Conference on Information Computing and Applications, ICICA 2010, held in Tangshan, China, in October 2010. The 76 papers are organized in topical sections on parallel and distributed computing; trusted and pervasive computing; internet and web computing; multimedia networking and computing; evolutionary computing and applications; scientific and engineering computing; and intelligent computing and applications.
Parallel and Distributed Computing -- Trusted and Pervasive Computing -- Internet and Web Computing -- Multimedia Networking and Computing -- Evolutionary Computing and Applications -- Scientific and Engineering Computing -- Intelligent Computing and Applications.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Software engineering; Information theory; Computer software; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Software Engineering/Programming and Operating Systems; Theory of Computation; Computer Systems Organization and Communication Networks